Shadows - Maya Zaharudin (MPH Group Publishing Sdn Bhd, 2017)
Poor Adam! First, he is teased by his brothers for being a coward and the next moment, he finds himself in a land of shadows wherea mysterious voice guides him as he goes on an adventure with a prince. Shadows is a magical adventure set in the world of wayang kulit — the ancient Malay art of shadow puppet plays — that adults and children can enjoy together.